Predictive Validity of Student Risk Screening Scale—Internalizing and Externalizing (SRSS-IE) Scores in Elementary Schools. (December 2019) - Lane, Kathleen Lynne; Oakes, Wendy Peia; Cantwell, Emily D.; Common, Eric A.; Royer, David J.; Leko, Melinda M.; Schatschneider, Christopher; Menzies, Holly Mariah; Buckman, Mark Matthew; Allen, Grant Edmund
In this article, we examined predictive validity of Student Risk Screening Scale—Internalizing and Externalizing (SRSS-IE) scores for use with elementary-age students ( N = 4, 465) from 14 elementary schools. Results indicated elementary school students with high levels of risk according to fall SRSS-IE scores—especially those with externalizing behaviors—were more likely to have lower oral reading fluency scores, lower Measures of Academic Progress (MAP) reading scores, more nurse visits, and more days spent in in-school suspension compared with students at low risk for externalizing or internalizing behaviors. Educational implications, limitations, and future directions are presented.